Devolution in the U.S. welfare reform: divergence and degradation in state benefits. - Ayala Cañón, Luis; Bárcena-Martín, Elena María; Martínez Vázquez, Jorge (Springer Nature, 2022)
The passage of the Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) in 1996 devolved responsibility for the design of welfare programs from the federal to state governments in the U.S. The strategies implemented to achieve some of the main goals of the reform might have had the effects of reducing the protection received by the most vulnerable households and increasing differences in benefit levels across states. We estimate these effects using Temporary Assistance for Needy Families data covering the two decades after the PRWORA’s enactment. We find that inequality levels across states increased and that a general process of degradation in the adequacy of these cash benefits took place ensuing devolution of welfare reform in the U.S.
Keywords: Delegación de poderes (Derecho administrativo); Asistencia social - Estados Unidos; Servicios sociales - Estados Unidos; Adequacy rates; Devolution; Re-ranking; TANF benefits; β-Convergence; σ- Divergence